2017
DOI: 10.1016/j.amepre.2016.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Compliance With and Enforcement of Graduated Driver Licensing Restrictions

Abstract: Introduction Graduated Driver Licensing (GDL) is the most effective strategy to reduce the burden of young driver crashes, but the extent to which young intermediate (newly licensed) drivers comply with and police enforce important GDL passenger and night-time restrictions is largely unknown. Population-level rates of intermediate drivers’ compliance were estimated as well as police enforcement among crash-involved drivers who were non-compliant. Methods New Jersey’s statewide driver licensing and crash data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Some participants thought that implementation of elements of the GDL regime might be unenforceable, but problems in enforcing regulations are not a reason for foregoing regulation. In other jurisdictions, non-compliance has been less an issue than predicted [ 40 , 41 ] although there have been some reports of ignoring restrictions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some participants thought that implementation of elements of the GDL regime might be unenforceable, but problems in enforcing regulations are not a reason for foregoing regulation. In other jurisdictions, non-compliance has been less an issue than predicted [ 40 , 41 ] although there have been some reports of ignoring restrictions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 In a series of previous papers, we demonstrated that this assumption is valid for the population of young intermediate drivers in NJ and that compliance with passenger and nighttime restrictions can be estimated using the QIE method. 11,14,19 Using these previously established methods, we identified all non-responsible 17-to 20-year-old intermediate drivers who were involved in a clean crash involving at least two vehicles from May 1, 2008 through April 30, 2012. For each study month, the prevalence of trip-level noncompliance was estimated as I i / N , where i is the restriction of interest, N is the total number of non-responsible intermediate drivers involved in clean multi-vehicle crashes, and I i is the number of these non-responsible intermediate drivers who were not in compliance with restriction i at the time of their crash.…”
Section: Methodsmentioning
confidence: 99%
“…Given that we were not able to confirm the presence of a parent/guardian, we conservatively estimated noncompliance based on the presence of more than one passenger when no passenger was aged 35 or older. 19…”
Section: Methodsmentioning
confidence: 99%
“…Research by Curry et al (2017) looked at traffic citations issued to intermediate drivers involved in a crash who were not compliant with night or passenger restrictions and concluded that there are low levels of police enforcement for the night driving and passenger restriction. In Massachusetts, the rate of citations issued to new drivers fell after the introduction of the GDL system despite there being no change in the number of driver licences issued (DePesa et al, 2017).…”
Section: Police and Enforcementmentioning
confidence: 99%